Global molecular variation of Paramecium jenningsi complex (Ciliophora, Protista): a starting point for further, detailed biogeography surveys. Issue 5 (4th July 2019) - PrzyboŚ, Ewa; Tarcz, Sebastian
Abstract : The world's second stand of P. primjenningsi ( Paramecium jenningsi complex, Ciliophora, Protista), heretofore known only from India, has been revealed in Ethiopia (Africa). This finding has enlarged the range of this cryptic species and was a trigger to re-analyse the distribution of all members of the complex (known from ∼20 tropical locations). The current survey is an initial one, where, based on haplotype networks, a detailed analysis of the relationship within the P. jenningsi complex has been performed. Although the V4 hypervariable fragment of the SSU rDNA gene is widely used as a first-step barcode marker for microbial HTS analyses, it has provided inconclusive results based on the dataset investigated. However, the ITS1-5.8S-ITS2-5'rDNA and COI mtDNA fragments indicate the possibility of the delimitation of the cryptic species of P. jenningsi (which is crucial from the point of view of metabarcoding surveys). We suppose that future sampling of unexplored, tropical regions will certainly change our knowledge about Paramecium biodiversity and biogeography. This sampling will probably rely on the integration of metabarcodes from environmental DNA studies, with molecular data obtained from identified representatives of particular cryptic species.